Angiogenic, apoptotic and autophagic profiling of chronic myeloid leukaemia patients’ platelets ex vivo before and after treatment with Imatinib - Joubert, Annie M. (University of Pretoria, 2022)
Thesis (PhD (Human Physiology))--University of Pretoria, 2022.